2014
DOI: 10.1155/2014/272814
|View full text |Cite|
|
Sign up to set email alerts
|

Algae Oil: A Sustainable Renewable Fuel of Future

Abstract: A nonrenewable fuel like petroleum has been used from centuries and its usage has kept on increasing day by day. This also contributes to increased production of greenhouse gases contributing towards global issues like global warming. In order to meet environmental and economic sustainability, renewable, carbon neutral transport fuels are necessary. To meet these demands microalgae are the key source for production of biodiesel. These microalgae do produce oil from sunlight like plants but in a much more effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 33 publications
(33 reference statements)
0
31
0
1
Order By: Relevance
“…To gain detailed analytical insight into the type and quantity of oxylipins in oils, the aim of the present study was to measure LA and ALA derived oxylipins in plant and algae oils containing varying amounts of LA and ALA at room temperature or after heating for 10 minutes with UPLC-MS/MS 27 . Algae oils were tested because they are an emerging and potentially sustainable source of dietary fat 28 . Thus, like plants, algae synthesize unsaturated fatty acids and contain oxygenase enzymes that may contribute to lipid oxidation during the extraction 29 .…”
Section: Introductionmentioning
confidence: 99%
“…To gain detailed analytical insight into the type and quantity of oxylipins in oils, the aim of the present study was to measure LA and ALA derived oxylipins in plant and algae oils containing varying amounts of LA and ALA at room temperature or after heating for 10 minutes with UPLC-MS/MS 27 . Algae oils were tested because they are an emerging and potentially sustainable source of dietary fat 28 . Thus, like plants, algae synthesize unsaturated fatty acids and contain oxygenase enzymes that may contribute to lipid oxidation during the extraction 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Animal fat sources include tallow, lard, poultry fat and fish oil [12]. The waste generated during their processing can be used for biodiesel production [11].…”
Section: Mutton Fat and Its Fatty Acid Componentmentioning
confidence: 99%
“…Seaweeds absorb light energy in the form of photons, which converts the inorganic compounds of CO 2 and water into sugars and oxygen. Thus produced sugar is further transformed as, complex carbohydrates, starches, proteins and lipids within the algal cells [63,64], S. wightii and G. corticata absorb the contaminants and biotransforms, thus leading to the concomitant propagation of biomass. In the present study, lipid accumulation in the thallus of seaweeds was observed in the culture amended with different oil concentrations which can be proved through further microscopic sections.…”
Section: Estimation Of Biochemical Constituentsmentioning
confidence: 99%